2020
DOI: 10.1007/s13365-020-00858-9
|View full text |Cite
|
Sign up to set email alerts
|

Miller Fisher syndrome diagnosis and treatment in a patient with SARS-CoV-2

Abstract: This case report describes the clinical characteristics of a 50-year-old woman that developed SARS-CoV-2 pneumonia and was admitted at the COVID-19 dedicated unit where she developed neurological symptoms 10 days after admission. After neurological examination, including a panel of blood cerebrospinal fluid biomarkers, a diagnosis of Miller Fisher syndrome (MFS) was hypothesized and intravenous immunoglobulin therapy (IVIG) was initiated. Fourteen days after the start of IVIG treatment, the patient has been di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 7 publications
0
65
1
4
Order By: Relevance
“…Persistence of LL areflexia and distal paraesthesia Lascano et al [ 31 ] RT-PCR + chest X-ray WBC 4000 cells/mm 3 ; lymphocytes 600 cells/mm 3 ; PC 322,000 cells/mm 3 NA Increased total protein (140 mg/dL), cell count: 4 cells/μL, negative SARS-CoV-2 PCR Demyelinating with sural sparing pattern AIDP Brain: no pathological findings Spinal cord: lumbosacral nerve root enhancement IVIG 400 mg/kg (5 days) Amoxicillin Improvement of tetraparesis and ability to walk with assistance. Persistence of neuropathic pain and distal paraesthesia Manganotti et al [ 32 ] RT-PCR + chest CT NA Negative anti-ganglioside antibodies negative serum anti-HIV, anti-HBV, anti-HCV antibodies Increased total protein (74.9 mg/dL), negative CSF PCR for bacteria, fungi, Mycobacterium tuberculosis , Herpes viruses, Enteroviruses, Japanese B virus and Dengue viruses NA Brain: no pathological findings IVIG 400 mg/kg (5 days) Lopinavir/ritonavir, hydroxychloroquine, antibiotic therapy, oxygen support (35%) Resolution of all symptoms except for minor hyporeflexia at the LL Manganotti et al [ 33 ] RT-PCR IL-1: 0.2 pg/ml (< 0.001 pg/ml), IL-6: 113.0 pg/ml (0.8–6.4 pg/ml), IL-8: 20.0 pg/ml (6.7–16.2 pg/ml), TNF-α: 16.0 pg/ml (7.8–12.2 pg/ml) Negative anti-ganglioside antibodies, negative HIV, HBV, HCV negative serological tests for autoimmune disorders Increased total protein (52 mg/dl), leucocytes: 1 cell/mm 3 , negative SARS-CoV-2 PCR Demyelinating AIDP NA IVIG 400 mg/kg/day (5 days) Hydroxychloroquine, oseltamivir, darunavir, methylprednisolone and tocilizumab + mechanical invasive ventilation Improvement of motor symptoms Manganotti et al [ 33 ] RT-PCR IL-1: 0.5 pg/ml (< 0.001 pg/ml), IL-6: 9.8 pg/ml (0.8–6.4 pg/ml), IL-8: 55.0 pg/ml (6.7–16.2 pg/ml), TNF- α: 16.0 pg/ml (7.8–12.2 pg/ml) Negativ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistence of LL areflexia and distal paraesthesia Lascano et al [ 31 ] RT-PCR + chest X-ray WBC 4000 cells/mm 3 ; lymphocytes 600 cells/mm 3 ; PC 322,000 cells/mm 3 NA Increased total protein (140 mg/dL), cell count: 4 cells/μL, negative SARS-CoV-2 PCR Demyelinating with sural sparing pattern AIDP Brain: no pathological findings Spinal cord: lumbosacral nerve root enhancement IVIG 400 mg/kg (5 days) Amoxicillin Improvement of tetraparesis and ability to walk with assistance. Persistence of neuropathic pain and distal paraesthesia Manganotti et al [ 32 ] RT-PCR + chest CT NA Negative anti-ganglioside antibodies negative serum anti-HIV, anti-HBV, anti-HCV antibodies Increased total protein (74.9 mg/dL), negative CSF PCR for bacteria, fungi, Mycobacterium tuberculosis , Herpes viruses, Enteroviruses, Japanese B virus and Dengue viruses NA Brain: no pathological findings IVIG 400 mg/kg (5 days) Lopinavir/ritonavir, hydroxychloroquine, antibiotic therapy, oxygen support (35%) Resolution of all symptoms except for minor hyporeflexia at the LL Manganotti et al [ 33 ] RT-PCR IL-1: 0.2 pg/ml (< 0.001 pg/ml), IL-6: 113.0 pg/ml (0.8–6.4 pg/ml), IL-8: 20.0 pg/ml (6.7–16.2 pg/ml), TNF-α: 16.0 pg/ml (7.8–12.2 pg/ml) Negative anti-ganglioside antibodies, negative HIV, HBV, HCV negative serological tests for autoimmune disorders Increased total protein (52 mg/dl), leucocytes: 1 cell/mm 3 , negative SARS-CoV-2 PCR Demyelinating AIDP NA IVIG 400 mg/kg/day (5 days) Hydroxychloroquine, oseltamivir, darunavir, methylprednisolone and tocilizumab + mechanical invasive ventilation Improvement of motor symptoms Manganotti et al [ 33 ] RT-PCR IL-1: 0.5 pg/ml (< 0.001 pg/ml), IL-6: 9.8 pg/ml (0.8–6.4 pg/ml), IL-8: 55.0 pg/ml (6.7–16.2 pg/ml), TNF- α: 16.0 pg/ml (7.8–12.2 pg/ml) Negativ...…”
Section: Resultsmentioning
confidence: 99%
“…Autonomic disturbances were rarely reported (16.7%, 12/72). In cases with MFS/MFS-GBS overlap, areflexia, oculomotor disturbances, and ataxia were present in 100% (9/9), 66.7% (6/9) and 66.7% (6/9), respectively [8,19,23,30,32,33,43,44]. The median of time to nadir was calculated in 40 patients with available data and resulted 4 days (IQR 3-9) ( Table 1).…”
Section: Clinical Features Of Gbs Spectrummentioning
confidence: 99%
“… 4 Auditory Impairment 2 Articles [ 62 ] [ 57 ] 5 NR in all articles. 5 Glossopharyngeal neuralgia 1 Article [ 57 ] 9 NR GBS and other Neuropathies 6 GBS and GBS variants 36 Articles [ 60 ], [ 63 ], [ 101 ], [ 191 ], [ 215 ], [ 218 ], [ 219 ], [ 220 ], [ 221 ], [ 222 ], [ 223 ], [ 224 ], [ 225 ], [ 226 ], [ 227 ], [ 228 ], [ 229 ], [ 230 ] [ 231 ] [ 232 ] [ 233 ] [ 234 ] [ 235 ] [ 236 ], [ 237 ], [ 238 ], [ 239 ], [ 240 ] [ 241 ] [ 242 ], [ 243 ], [ 244 ] [ 245 ] [ 246 ], [ 247 ], [ 248 ] 52 NR in all articles. Su XW et al [ 226 ], reoorted a patient GBS with dysautonomia.…”
Section: Resultsmentioning
confidence: 99%
“…( Table 4 ) Miller Fisher Syndrome was also reported in several cases. [ 101 , 228 , 237 , 239 , 246 ]…”
Section: Resultsmentioning
confidence: 99%
“…In light with this observations, we recently review the appearance of autoimmune diseases/disorders reported to be triggered by the SARS-CoV-2 infection [ 34 ] ( Table 1 ). Autoimmune disorders such as: Guillain-Barré syndrome [ 35 , 36 ], Miler Fisher Syndrome (MFS) [ 37 ], Antiphospholipid syndrome [ 14 ], Immune thrombocytopaenic purpura [ 38 , 39 ], systemic lupus erythematosus (SLE) [ 40 ] and Kawasaki disease [ 41 , 42 ] – have been reported in patients with COVID-19 infection.…”
Section: The Development Of Autoimmune Diseases Secondary To Covid-19mentioning
confidence: 99%